Progressive technologies of coal, coalbed methane, and ores mining - Bondarenko, Volodymyr; Kovalevs'ka, Iryna; Ganushevych, Kostiantyn (CRC Press, 2014)
Presenting new technologies in underground coal extraction, with special attention to mine galleries support and maintenance, load mechanism of ""massif-support system-safety system"" systems, analysis of face equipment for thin coal seams mining and substantiation of rational stoping parameters. Advanced surface mining technologies of coal and ore are discussed in an original form, stability calculations of internal dumps and open-cut faces are presented, as well as examination of land surface subsidence using modern methods of calculation experiments. Special attention is given to the comple
Keywords: Coal mines and mining.; Coal mines and mining -- Safety measures.; elektronické knihy; electronic books